A high current common mode inductor and its preparation method
Through the innovation of FeCo composite materials and packaging structure, the problems of saturation and leakage current of common-mode inductors in high-current and high-power circuits are solved, and efficient filtering performance is achieved, which is suitable for high-power circuits.
Patent Information
- Application Number
- CN202211733111.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2042-12-30
AI Technical Summary
Existing common-mode inductors are easily saturated in high-current and high-power circuits, resulting in increased leakage current and making it difficult to meet the filtering performance requirements of EMC design.
FeCo composite material is used as the core material, and the grains are refined by doping Si and B elements to form an insulating oxide layer. A composite coating of nano-oxide, phosphate and borosilicate glass is used, combined with a packaging structure to increase the inductance value and reduce eddy current.
The operating current capability of the common-mode inductor is improved, the leakage current is reduced, the filtering performance requirements of high-power circuits are met, and it is suitable for high-current application scenarios.
Smart Images

Figure CN115831521B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of common-mode inductors, and in particular to a high-current common-mode inductor and a preparation method thereof. Background Art
[0002] To meet EMC requirements, electronic products (such as power supplies) often employ common-mode inductors to filter common-mode electromagnetic interference signals. Conventional power supply products employ common-mode inductors with two windings wound on either side of the magnetic core. The large gap between the two windings creates magnetic flux leakage, also known as leakage inductance, also known as differential-mode inductance. Therefore, common-mode inductors generally have considerable differential-mode interference attenuation capabilities. Leakage inductance is often utilized in filters. For example, in typical filter designs, a common-mode inductor is used to generate an appropriate amount of differential-mode inductance through the leakage inductance of the common-mode inductor to suppress differential-mode interference.
[0003] However, as power supplies become increasingly powerful, operating currents are also increasing. Conventional ferrite cores are prone to saturation, and require gaps to prevent magnetic saturation caused by current spikes, which can easily lead to large leakage currents. Alloy cores, on the other hand, have lower permeability, often requiring more copper wire windings, which can lead to higher DCR values for common-mode inductors. Therefore, using only ferrite or alloy materials cannot fully meet application requirements.
[0004] Therefore, the existing technology has defects and needs to be improved. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a high-current common-mode inductor and a preparation method thereof, which meet the device requirements for common-mode inductor filtering performance and are particularly suitable for application scenarios of high-power circuit filtering.
[0006] The technical solution of the present invention is as follows: a method for preparing a high-current common-mode inductor is provided, comprising the following steps.
[0007] S1: The first magnet powder is mixed with nano oxide and coating agent by ball milling and then dried, and then mixed with 0.5-2um borosilicate glass to form a first mixed powder, wherein the coating agent is a mixture of a first phosphate and magnesium oxide or sodium silicate; the composition of the first magnet powder is 75.7-86.0wt% Fe, 11.0-15.0wt% Co, 1.5-4.0wt% Si, 1.0-3.5wt% Cr, and 0.5-1.8wt% B; the second magnet powder is mixed with the second phosphate by ball milling and then dried, and then mixed with 2-6um carbonyl iron powder to form a second mixed powder; the composition of the second magnet powder is: 85.90-91.95wt% Fe, 6.5-10.5wt% Si, 1.5-3.5wt% Cr, and 0.05-0.1wt% B.
[0008] S2: adding the first mixed powder to the first adhesive, mixing, and drying the resin to form granulated powder for the wound magnet; adding the second mixed powder to the second adhesive, mixing, and drying the resin to form raw material powder for the packaged magnet.
[0009] S3: The granulated powder is pressed into shape at a pressure of 1800-2500 MPa and annealed in a nitrogen atmosphere at 750-850°C for 30-90 minutes to form a wound magnet. Annealing repairs defects in the first magnet powder caused by the ball milling process, thereby improving the magnetic properties of the first magnet powder. During the annealing process, part of the first binder decomposes, producing oxygen. The Cr doped in the first magnet powder segregates within the particles during annealing, combining with the oxygen to form an insulating oxide layer that provides inter-particle insulation and further reduces inter-particle eddy currents.
[0010] S4: Wind the wound magnet evenly into a flat coil to form a winding.
[0011] S5: After the wound magnet with the winding is inserted into the bottom shell, the wire legs of the winding are fixed to the bottom shell to form a semi-finished product.
[0012] S6: Place the semi-finished product into a mold, and add raw material powder of the encapsulated magnet into the mold, and encapsulate it at a temperature of 120°C to 180°C and a pressure of 10 to 30 MPa to form a large current common mode inductor.
[0013] Furthermore, the particle size of the first magnet powder is less than 57 μm, and the particle size of the second magnet powder is less than 28 μm.
[0014] Furthermore, the nano-oxide is at least one of silicon oxide, aluminum oxide, and titanium oxide, the particle size of the nano-oxide is less than 150 nm, and the addition ratio of the nano-oxide is 0.2 wt% to 0.7 wt% of the weight of the first magnet powder.
[0015] Furthermore, the first phosphate is at least one of aluminum dihydrogen phosphate, manganese dihydrogen phosphate, and zinc phosphate. The magnesium oxide, serving as a curing agent for the first phosphate, is added in an amount of 1.5 to 4.0 weight percent based on the weight of the phosphate. The sodium silicate or the first phosphate mixture is added in an amount of 0.6 to 1.5 weight percent based on the weight of the first magnet powder. Wet ball milling is preferably employed, and the milling medium can be a mixture of ethanol and water. Due to the presence of water, the first phosphate dissolves in the water. After ball milling and drying, the magnesium oxide adheres to the surface of the first magnet powder, and the first phosphate adheres to the magnesium oxide, effectively coating the first magnet powder with the first phosphate.
[0016] Furthermore, the borosilicate glass is at least one of alkaline earth borosilicate glass and low borosilicate glass, and the addition ratio of the borosilicate glass is 0.5 wt% to 1.5 wt% of the powder weight.
[0017] Furthermore, the first adhesive includes: a first silicone resin and PVB, the first silicone resin is an alkaline silicone resin, the addition ratio of the first adhesive is 0.2wt% to 0.5wt% of the weight of the first mixed powder, and the weight ratio of silicone resin to PVB in the first adhesive is 1:2 to 1:5.
[0018] Furthermore, the second phosphate is at least one of zinc phosphate, manganese phosphate, and sodium dihydrogen phosphate, and the addition ratio of the second phosphate is 0.3 wt% to 0.8 wt% of the weight of the second magnet powder.
[0019] Furthermore, the carbonyl iron powder is a powder passivated with phosphoric acid, and its volume resistivity is greater than 105Ω·m. The addition ratio of the carbonyl iron powder is 22wt% to 38wt% of the weight of the second magnet powder.
[0020] Furthermore, the second adhesive includes: a second silicone resin and an epoxy resin, the second silicone resin is an alkaline organic silicone resin, the epoxy resin is a low-melting-point thermosetting resin, the addition ratio of the second adhesive is 3.5wt% to 6.5wt% of the weight of the second mixed powder, and the weight ratio of silicone resin to epoxy resin in the second adhesive is 1:4 to 1:8.
[0021] The core material of the wound magnet is FeCo composite material, which has a larger saturation magnetic flux density and greatly improves the working current of the product. At the same time, by doping Si and B elements, the grain size inside the particles can be refined, eddy currents can be reduced, and the frequency of material use can be increased. The first magnet powder needs to undergo heat treatment during the powder making process. The oxidation segregation of the doped Cr element during heat treatment forms an insulating oxide layer, which can provide insulation between particles and further reduce the eddy currents between particles, so that FeCo materials can be used at frequencies of hundreds of kHz. A dense coating layer is formed between particles through the composite coating of nano-oxides, phosphates and borosilicate glass to further reduce the eddy currents between particles and increase the application frequency of the material. The effective inductance value of the inductor is increased through the packaging structure while reducing the leakage current, reducing the superimposed magnetic field effect of the leakage current and the working current, thereby achieving the effect of improving the working current of the product, meeting the device's requirements for common-mode inductor filtering performance, and is particularly suitable for high-power circuit filtering applications.
[0022] The present invention also provides a high-current common-mode inductor, which is manufactured using the above-mentioned method for manufacturing the high-current common-mode inductor.
[0023] By adopting the above scheme, the present invention provides a high-current common-mode inductor and a preparation method thereof. The core material of the wound magnet is an FeCo composite material, which has a larger saturation magnetic flux density and greatly improves the working current of the product. At the same time, by doping Si elements and B elements, the grain size inside the particles can be refined, the eddy current can be reduced, and the use frequency of the material can be increased. The first magnet powder needs to be heat-treated during the powder making process. The oxidation segregation of the doped Cr element during the heat treatment forms an insulating oxide layer, which can provide insulation between the particles and further reduce the eddy current between the particles, so that the FeCo material can be used at a frequency of hundreds of kHz. A dense coating layer is formed between the particles through the composite coating of nano-oxides, phosphates and borosilicate glass, which further reduces the eddy current between the particles and increases the application frequency of the material. The effective inductance value of the inductor is increased while the leakage current is reduced through the packaging structure, and the superimposed magnetic field effect of the leakage current and the working current is reduced, thereby achieving the effect of improving the working current of the product, meeting the device's requirements for common-mode inductor filtering performance, and is particularly suitable for application scenarios of high-power circuit filtering. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the structure of an embodiment of the present invention without the top packaging magnet;
[0025] Figure 2 for Figure 1 A structural diagram of another perspective of the embodiment;
[0026] Figure 3 for Figure 1 Cross-sectional view of an embodiment. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] Example 1
[0029] A first magnet powder having a composition of 75.7wt% Fe, 15.0wt% Co, 4.0wt% Si, 3.5wt% Cr, and 1.8wt% B is selected. The maximum particle size of the first magnet powder is less than 57um. The first magnet powder is ball-milled with a mixture of nano-oxide, first phosphate, and magnesium oxide, dried, and mixed with 2um borosilicate glass to form a first mixed powder; the nano-oxide can be aluminum oxide, and the particle size of the nano-oxide is less than 150nm. The addition ratio of the nano-oxide is 0.2wt% of the weight of the magnet material. The first phosphate is dilute aluminum phosphate, and the addition amount of magnesium oxide as a curing agent of the first phosphate is 1.5wt% of the weight of the first phosphate, and the addition ratio of the first phosphate is 0.6wt% of the weight of the first magnet powder. The borosilicate glass can be alkaline earth borosilicate glass. The addition ratio of the borosilicate glass is 0.5wt% of the weight of the first magnet powder. A first mixed powder is added to a silicone resin and PVB, mixed, and dried to form a granulated powder for a wound magnet 1. The silicone resin is an alkaline organic silicone resin such as KR-242A, and the PVB is a low molecular weight polyvinyl butyral ester such as B-98. The silicone resin and PVB solution is added in a ratio of 0.2 wt% to the weight of the first mixed powder, with a weight ratio of silicone resin to PVB of 1:2. The granulated powder is pressed into shape using a pressure of 2500 MPa and annealed at 850°C in a nitrogen atmosphere for 30 minutes to form the wound magnet 1. The wound magnet 1 is then uniformly wound into two sets of flat coils to form a winding 2. The flat coils are 0.2 mm thick, 1.5 mm wide, and have 31 turns. The magnet 1 with the winding 2 is then inserted into a plastic base 3, and the winding legs 6 are secured to the base to form a semi-finished product. A second magnetic powder having a composition of 91.95wt% Fe, 6.5wt% Si, 1.5wt% Cr, and 0.05wt% B is selected. The maximum particle size of the second magnetic powder is less than 28um. The second magnetic powder is ball-milled with a second phosphate and then dried, and then mixed with 6um carbonyl iron powder to form a mixed powder; the second phosphate is zinc phosphate, and the addition ratio of the second phosphate is 0.8wt% of the weight of the magnetic powder; the carbonyl iron powder is a powder passivated with phosphoric acid, and its volume resistivity is greater than 105Ω·m, and the addition ratio of the carbonyl iron powder is 38wt% of the weight of the second magnetic powder. The second mixed powder is added to a second silicone resin and an epoxy resin, and the resin is dried to form a raw material powder for encapsulating the magnet 4. The second silicone resin is an alkaline silicone resin KR-242A, the epoxy resin is a low-melting-point thermosetting resin such as E44, the addition ratio of the mixed solution of the second silicone resin and the epoxy resin is 3.5wt% of the powder weight, and the weight ratio of the second silicone resin to the epoxy resin is 1:4.The semi-finished product consisting of wound magnet 1 and winding 2 is placed in a mold. The raw material powder for encapsulated magnet 4 is then encapsulated at 120°C and 30 MPa to form a common-mode inductor test sample. The product is 21mm high, 11.5mm wide, and 4.5mm deep. (See the product for details.) Figure 1-Figure 3 .
[0030] Example 2
[0031] A first magnet powder having a composition of 86.0wt% Fe, 11.0wt% Co, 1.5wt% Si, 1.0wt% Cr, and 0.5wt% B is selected. The maximum particle size of the first magnet powder is less than 57um. The first magnet powder is ball-milled with a mixture of nano-oxide, a first phosphate, and magnesium oxide, dried, and mixed with 0.5um borosilicate glass to form a first mixed powder; the nano-oxide is silicon oxide, and the particle size of the nano-oxide is less than 150nm. The addition ratio of the nano-oxide is 0.7wt% of the weight of the magnet material. The first phosphate is zinc phosphate, and the addition amount of magnesium oxide as a curing agent of the first phosphate is 4.0wt% of the weight of the first phosphate, and the addition ratio of the mixture of the first phosphate and magnesium oxide is 1.5wt% of the weight of the first magnet powder. The borosilicate glass is low-borosilicate glass. The addition ratio of the borosilicate glass is 1.5wt% of the weight of the first magnet powder. A first mixed powder is added to a first silicone resin and PVB, mixed, and dried to form a granulated powder for a wound magnet 1; the first silicone resin is an alkaline organic silicone resin such as ES1023, and the PVB is a low molecular weight polyvinyl butyral ester such as B-76. The mixed solution of the first silicone resin and PVB is added in a ratio of 0.2 wt% to the weight of the first mixed powder, with a weight ratio of silicone resin to PVB of 1:5. The granulated powder is pressed into shape using a pressure of 1800 MPa and annealed at 750°C in a nitrogen atmosphere for 90 minutes to form the wound magnet 1. The wound magnet 1 is then uniformly wound into two sets of flat coils to form windings 2, each with a thickness of 0.2 mm, a flat wire width of 1.5 mm, and 31 turns. The magnet 1 with windings 2 is then inserted into a plastic base 3, and the winding legs 6 are secured to the base to form a semi-finished product. A second magnet powder with a composition of 85.90wt% Fe, 10.5wt% Si, 3.5wt% Cr, and 0.1wt% B is selected. The maximum particle size of the second magnet powder is less than 28um. The second magnet powder is ball-milled with a second phosphate and then dried, and then mixed with 2um carbonyl iron powder to form a second mixed powder; the second phosphate is sodium diphosphate, and the addition ratio of the second phosphate is 0.3wt% of the weight of the second magnet powder; the carbonyl iron powder is a powder passivated with phosphoric acid, and its volume resistivity is greater than 105Ω·m, and the addition ratio of the carbonyl iron powder is 22wt% of the weight of the second magnet powder. The second mixed powder is added to a second silicone resin and an epoxy resin, and the resin is dried to form the raw material powder for encapsulating the magnet 4. The second silicone resin is an alkaline silicone resin such as ES1023, and the epoxy resin is a low-melting-point thermosetting resin such as E51. The addition ratio of the second silicone resin and the epoxy resin is 6.5wt% of the powder weight, and the weight ratio of the second silicone resin to the epoxy resin is 1:8.The semi-finished product consisting of wound magnet 1 and winding 2 is placed in a mold. The raw material powder for encapsulated magnet 4 is then encapsulated at 180°C and 10 MPa to form a common-mode inductor test sample. The product is 21mm high, 11.5mm wide, and 4.5mm deep. (See the product diagram for details.) Figure 1-Figure 3 .
[0032] Example 3
[0033] A first magnet powder having a composition of 79.6wt% Fe, 13.5wt% Co, 3.0wt% Si, 2.5wt% Cr, and 1.4wt% B is selected. The maximum particle size of the first magnet powder is less than 57um. The first magnet powder is ball-milled with a mixture of nano-oxides and sodium silicate, dried, and mixed with 1um borosilicate glass to form a first mixed powder; wherein the nano-oxide is titanium oxide, and the particle size of the nano-oxide is less than 150nm. The addition ratio of the nano-oxide is 0.5wt% of the weight of the first magnet powder. The addition ratio of sodium silicate is 1.0wt% of the weight of the first magnet powder. The borosilicate glass can be low-borosilicate glass. The addition ratio of the borosilicate glass is 1.0wt% of the weight of the first magnet powder. A first mixed powder is added to a first silicone resin and PVB, mixed, and dried to form a granulated powder for a wound magnet 1. The first silicone resin is an alkaline organic silicone resin such as KR-311, and the PVB is a low molecular weight polyvinyl butyral ester such as B-44. The silicone resin and PVB are added in a ratio of 0.35 wt% to the weight of the first magnet powder, with a weight ratio of silicone resin to PVB of 1:3. The granulated powder is pressed into shape at a pressure of 2000 MPa and annealed at 800°C in a nitrogen atmosphere for 60 minutes to form a wound magnet 1. The wound magnet 1 is then uniformly wound into two sets of flat coils to form a winding 2. The flat coils are 0.2 mm thick, 1.5 mm wide, and have 31 turns. The magnet 1 with winding 2 is then inserted into a plastic base case 3, and the winding legs 6 are secured to the base case to form a semi-finished product. A second magnet powder having a composition of 88.92 wt% Fe, 8.5 wt% Si, 2.5 wt% Cr, and 0.08 wt% B is selected. The maximum particle size of the second magnet powder is less than 28 μm. The second magnet powder is ball-milled with phosphate and then dried, and then mixed with 4 μm carbonyl iron powder to form a second mixed powder; wherein the phosphate is manganese phosphate, and the addition ratio of the phosphate is 0.6 wt% of the weight of the second magnet powder; wherein the carbonyl iron powder is a powder passivated with phosphoric acid, and its volume resistivity is greater than 105 Ω·m, and the addition ratio of the carbonyl iron powder is 29 wt% of the weight of the second magnet powder. The second mixed powder is added with silicone resin and epoxy resin, mixed, and the resin is dried to form the raw material powder for encapsulating the magnet 4. The second silicone resin is an alkaline organic silicone resin such as KR-311, and the epoxy resin is a low-melting-point thermosetting resin such as bisphenol A novolac epoxy resin. The addition ratio of the second silicone resin to the epoxy resin is 5.0wt% of the weight of the second magnet powder, and the weight ratio of the second silicone resin to the epoxy resin is 1:6. The semi-finished product formed by the wound magnet 1 and the winding 2 is placed in a mold, and the raw material powder of the encapsulated magnet 4 is encapsulated at a temperature of 150°C and a pressure of 20MPa to form a common-mode inductor test sample. The product is 21mm high, 11.5mm wide, and 4.5mm high. Please refer to Figure 1-Figure 3 .
[0034] Comparative Example 1
[0035] The composition of the magnetic material is selected to be 75.7wt% Fe, 15.0wt% Co, 4.0wt% Si, 3.5wt% Cr, and 1.8wt% B. The maximum particle size of the magnetic material powder is less than 57um. The magnetic material is mixed with a mixture of nano-oxides, sodium silicate, or phosphate and magnesium oxide by ball milling, dried, and mixed with 2um borosilicate glass to form a mixed powder; the nano-oxides can be insulating materials with high volume resistivity such as silicon oxide, aluminum oxide, titanium oxide, and the particle size of the nano-oxides is less than 150nm. The addition ratio of the nano-oxides is 0.2wt% of the weight of the magnetic material. The phosphate is dihydrogen aluminum phosphate, and the addition amount of magnesium oxide as a curing agent of the phosphate is 1.5wt% of the weight of the phosphate. The addition ratio of sodium silicate is 0.6wt% of the weight of the magnetic material. The borosilicate glass can be alkaline earth borosilicate glass. The addition ratio of the borosilicate glass is 0.5wt% of the weight of the magnetic material. Add silicone resin and PVB to the mixed powder and dry the resin to form a granulated powder material of the magnet 1; wherein the silicone resin is an alkaline organic silicone resin such as KR-242A, wherein PVB is a low molecular weight polyvinyl butyral ester such as B-98, wherein the mixed solution of silicone resin and PVB is added in an amount of 0.2wt% of the powder weight, wherein the weight ratio of silicone resin to PVB in the mixed solution is 1:2. The granulated powder is pressed into shape by a pressure of 2500MPa and annealed in a mixed atmosphere of nitrogen at 850°C for 30 minutes to form a wound magnet 1. The wound magnet 1 is evenly wound into two groups of flat coils to form a winding 2, wherein the thickness of the flat coil is 0.2mm, the width of the flat wire is 1.5mm, and the number of turns is 31. After the magnet 1 with the winding 2 is inserted into the plastic bottom shell 3, the winding wire pins 6 are fixed to the bottom shell to form a common mode inductance test sample. The product height is 21mm, the product width is 11.5mm, and the product height is 4.5mm. Please refer to Figure 1-Figure 3 .
[0036] Comparative Example 2
[0037] The material composition is a commercially available alloy material (wherein the Fe content is 93.5-96.5wt%, and the Si content is 3.5-6.5wt%). The powder is added with an epoxy resin solution containing 0.07wt% of the powder weight, mixed in a mixer for 45 minutes to obtain a mixed powder, and dried under vacuum at 70°C for 2.5 hours to obtain a mixed powder, wherein the C residual content of the epoxy resin after calcination at 600°C is less than 830ppm. The obtained mixed powder is pressed into an embryo body in a mold using 1800MPa, and the embryo body is nitrogen sintered at 750°C for 2.5 hours to obtain a wound magnet 1, and the wound magnet 1 is evenly wound with 2 groups of flat coils to form a winding 2, wherein the flat coil is 0.2mm thick, the flat wire is 1.5mm wide, and the number of turns is 31. After the magnet 1 with the winding 2 is inserted into the plastic bottom shell 3, the winding wire pins 6 are fixed to the bottom shell to form a common mode inductance test sample. The product height is 21mm, the product width is 11.5mm, and the product height is 4.5mm. Figure 1-Figure 3 Performance tests were conducted on Examples 1-3 and Comparative Examples 1-2, and the test structures are shown in Table 1.
[0038] Table 1
[0039] Test items unit Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Inductance value 1-4 pins mH 10 10 10 6.9 6.2 Inductance value 2-3 pin mH 10 10 10 6.9 6.2 Inductance value 1-4 pins (5A) mH 7.1 7.3 7.4 4.9 3.7 Inductance value 2-3 pins (5A) mH 7.1 7.3 7.4 4.9 3.7
[0040] As can be seen from Table 1, Examples 1-3 have better inductance performance than Comparative Examples 1-2; and under high current conditions, they also have better inductance performance, which can improve the working current of the product, meet the device's requirements for common-mode inductance filtering performance, and are particularly suitable for application scenarios of high-power circuit filtering.
[0041] In summary, the present invention provides a large current common-mode inductor and a preparation method thereof. The core material of the wound magnet is an FeCo composite material, which has a larger saturation magnetic flux density and greatly improves the working current of the product. At the same time, by doping Si elements and B elements, the grain size inside the particles can be refined, the eddy current can be reduced, and the use frequency of the material can be increased. The first magnet powder needs to be heat-treated during the powder making process. The oxidation segregation of the doped Cr element during the heat treatment forms an insulating oxide layer, which can provide insulation between the particles and further reduce the eddy current between the particles, so that the FeCo material can be used at a frequency of hundreds of kHz. A dense coating layer is formed between the particles through the composite coating of nano-oxides, phosphates and borosilicate glass to further reduce the eddy current between the particles and increase the application frequency of the material. The effective inductance value of the inductor is increased while the leakage current is reduced through the packaging structure, and the superimposed magnetic field effect of the leakage current and the working current is reduced, thereby achieving the effect of improving the working current of the product, meeting the device's requirements for common-mode inductor filtering performance, and is particularly suitable for application scenarios of high-power circuit filtering.
[0042] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high current common mode inductor, characterized in that: The following steps are involved: S1: The first magnet powder is mixed with nano-oxide and a coating agent by ball milling and then dried, and then mixed with 0.5-2 μm borosilicate glass to form a first mixed powder, wherein the coating agent is a mixture of a first phosphate and magnesium oxide or sodium silicate; the composition of the first magnet powder is 75.7-86.0 wt% Fe, 11.0-15.0 wt% Co, 1.5-4.0 wt% Si, 1.0-3.5 wt% Cr, and 0.5-1.8 wt% B; the second magnet powder is mixed with a second phosphate by ball milling and then dried, and then mixed with 2-6 μm carbonyl iron powder to form a second mixed powder; the composition of the second magnet powder is: 85.90-91.95 wt% Fe, 6.5-10.5 wt% Si, 1.5-3.5 wt% Cr, and 0.05-0.1 wt% B; S2: adding the first mixed powder to the first adhesive, mixing, and drying the resin to form granulated powder for the wound magnet; adding the second mixed powder to the second adhesive, mixing, and drying the resin to form raw material powder for the encapsulated magnet; S3: pressing the granulated powder into a shape at a pressure of 1800-2500 MPa and annealing the shape in a nitrogen atmosphere at 750-850° C. for 30-90 minutes to form a wound magnet; S4: Winding the wound magnet evenly into a flat coil to form a winding; S5: inserting the wound magnet with the winding into the bottom shell and fixing the winding wire legs to the bottom shell to form a semi-finished product; S6: Place the semi-finished product into a mold, add the raw material powder of the encapsulated magnet into the mold, and encapsulate it at a temperature of 120°C to 180°C and a pressure of 10~30MPa to form a high current common mode inductor; The nano-oxide is at least one of silicon oxide, aluminum oxide, and titanium oxide. The particle size of the nano-oxide is less than 150 nm. The addition ratio of the nano-oxide is 0.2 wt% to 0.7 wt% of the weight of the first magnet powder.
2. The method for preparing a high current common mode inductor according to claim 1, characterized in that: The particle size of the first magnet powder is less than 57 μm, and the particle size of the second magnet powder is less than 28 μm.
3. The method for preparing a high current common mode inductor according to claim 1, characterized in that: The first phosphate is at least one of aluminum dihydrogen phosphate, manganese dihydrogen phosphate, and zinc phosphate. The magnesium oxide is used as a curing agent for the first phosphate and its addition amount is 1.5wt%~4.0wt% of the weight of the phosphate. The addition ratio of the sodium silicate or the first phosphate mixture is 0.6wt%~1.5wt% of the weight of the first magnet powder.
4. The method for preparing a high current common mode inductor according to claim 1, wherein: The borosilicate glass is at least one of alkaline earth borosilicate glass and low borosilicate glass; the addition ratio of the borosilicate glass is 0.5wt% to 1.5wt% of the powder weight.
5. The method for preparing a high current common mode inductor according to claim 1, wherein: The first adhesive includes: a first silicone resin and PVB, the first silicone resin is an alkaline organic silicone resin, the addition ratio of the first adhesive is 0.2wt%~0.5wt% of the weight of the first mixed powder, and the weight ratio of silicone resin to PVB in the first adhesive is 1:2~1:
5.
6. The method for preparing a high current common mode inductor according to claim 1, characterized in that: The second phosphate is at least one of zinc phosphate, manganese phosphate, and sodium dihydrogen phosphate, and the addition ratio of the second phosphate is 0.3 wt % to 0.8 wt % of the weight of the second magnet powder.
7. The method for preparing a high current common mode inductor according to claim 1, characterized in that: The carbonyl iron powder is a powder passivated with phosphoric acid, and its volume resistivity is greater than 105Ω·m. The addition ratio of the carbonyl iron powder is 22wt% to 38wt% of the weight of the second magnet powder.
8. The method for preparing a high current common mode inductor according to claim 1, characterized in that: The second adhesive includes: a second silicone resin and an epoxy resin, the second silicone resin is an alkaline organic silicone resin, the epoxy resin is a low-melting-point thermosetting resin, the addition ratio of the second adhesive is 3.5wt%~6.5wt% of the weight of the second mixed powder, and the weight ratio of silicone resin to epoxy resin in the second adhesive is 1:4~1:
8.
9. A high current common mode inductor, characterized in that: The high-current common-mode inductor is manufactured using the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Soft magnetic alloy material, preparation method and application thereof
CN112509777A
Method of manufacturing dust core and dust core
JP2005303006A